2018
DOI: 10.1253/circj.cj-17-0760
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of CRUSADE, ACTION and ACUITY-HORIZONS Bleeding Risk Scores in Chinese Patients With ST-Segment Elevation Myocardial Infarction

Abstract: Background:The CRUSADE, ACTION and ACUITY-HORIZONS bleeding scores have been derived using Caucasian patients, and little is known about which has the better predictive ability in Chinese patients, especially for patients with STEMI. Methods and Results:We retrospectively analyzed 2,208 consecutive STEMI patients undergoing primary PCI (PPCI). Major bleeding events were defined according to Bleeding Academic Research Consortium criteria (type 3 or 5). Predictive ability of the 3 scores was assessed using logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
(15 reference statements)
0
3
1
1
Order By: Relevance
“…Several studies have compared both scores, finding a similar predictive capacity. (20,21) A recent meta-analysis, (19) of 17 studies with more than 18 thousand patients, reported a moderate predictive capacity of both scores (AUC 0.71 and 0.76, respectively), somewhat higher than that found in our work (0.68 and 0.70).…”
Section: Action_gwtg Orbit Crusadecontrasting
confidence: 67%
“…Several studies have compared both scores, finding a similar predictive capacity. (20,21) A recent meta-analysis, (19) of 17 studies with more than 18 thousand patients, reported a moderate predictive capacity of both scores (AUC 0.71 and 0.76, respectively), somewhat higher than that found in our work (0.68 and 0.70).…”
Section: Action_gwtg Orbit Crusadecontrasting
confidence: 67%
“…(18,19) El ACTION-GWTG fue desarrollado incluyendo pacientes con SCA con y sin elevación de ST. Varios estudios han comparado ambos scores encontrando similar capacidad predictiva. (20,21)Un metaanálisis reciente, (19) sobre 17 estudios con más de 18 mil pacientes, reportó una moderada capacidad predictiva en ambos scores (ABC: 0,71 y 0,76, respectivamente), algo mayor que la encontrada en nuestro trabajo (0,68 y 0,70).…”
Section: Discussionunclassified
“…12,13) A recent Chinese cohort study by Liu, et al also showed CRUSADE and ACTION scores having greater predictive ability for in-hospital major bleeding than the ACUITY-HORIZONS RS in Chinese STEMI patients undergoing PCI. 14) However, different from the study of Liu, et al, our study cohort included both STEMI and NSTEMI patients. Compared with NSTEMI patients, STEMI patients generally have a lower prevalence of comorbidities and shorter hospital-associated delays.…”
Section: Comparison Of Rsmentioning
confidence: 98%